2018
DOI: 10.1088/1674-1056/27/1/014401
|View full text |Cite
|
Sign up to set email alerts
|

A review of recent theoretical and computational studies on pinned surface nanobubbles

Abstract: The findings of long-lived surface nanobubbles in various experiments brought a puzzle in theory, as they were supposed to be dissolved in microseconds due to the high Laplace pressure. However, an increasing number of studies suggest that the pinning of contact line, together with certain levels of oversaturation, is responsible for the anomalous stability of surface nanobubble. This mechanism can interpret most characteristics of surface nanobubbles. Here we summarize recent theoretical and computational wor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 95 publications
0
11
0
2
Order By: Relevance
“…Combining these observations with the zeta potential results, it can be concluded that the nanobubbles and sodium oleate molecules are found to interact in solution, forming a hydrophobic group of sodium oleate molecules directed into the interior of the nanobubbles and a hydrophilic group exposed to the solution with a negatively charged nanobubble inclusion. As the hydrophilic group (carboxyl group) in the nanobubble inclusion interacts strongly with the surface of the mica, including electrostatic attraction, hydrogen bonding, and chemical bond forces of the carboxyl and mica surface atoms, the entire nanobubble inclusion is adsorbed on the mica surface. The adsorption morphology of the sodium oleate and nanobubble solution on the mica surface at higher concentration is shown in Figure f.…”
Section: Resultsmentioning
confidence: 99%
“…Combining these observations with the zeta potential results, it can be concluded that the nanobubbles and sodium oleate molecules are found to interact in solution, forming a hydrophobic group of sodium oleate molecules directed into the interior of the nanobubbles and a hydrophilic group exposed to the solution with a negatively charged nanobubble inclusion. As the hydrophilic group (carboxyl group) in the nanobubble inclusion interacts strongly with the surface of the mica, including electrostatic attraction, hydrogen bonding, and chemical bond forces of the carboxyl and mica surface atoms, the entire nanobubble inclusion is adsorbed on the mica surface. The adsorption morphology of the sodium oleate and nanobubble solution on the mica surface at higher concentration is shown in Figure f.…”
Section: Resultsmentioning
confidence: 99%
“…11. [179][180][181] If the internal pressure is not in balance with the degree of gas saturation in the surrounding liquid, the bubble gas should dissolve into the liquid, making the bubble smaller down to complete dissolution. The internal pressure of nanobubbles is, however, anomalously high, since an unrealistic supersaturation degree of the liquid would be required to ensure their existence.…”
Section: Bubble Mechanism: the Existential Crisis Of Nanobubblesmentioning
confidence: 99%
“…Molecular simulations have the spatial resolution to address these questions. However, while several computational studies have been carried out to shed light on the unexpected stability and nucleation of nanobubbles, the nucleation and stationary states of electrochemically generated nanobubbles have never been studied by molecular simulations. In this work, we investigate the nucleation and stationary states of electrochemically generated nanobubbles, using molecular dynamics simulations with an algorithm that mimics the electro-generation of gas at the electrode.…”
Section: Introductionmentioning
confidence: 99%